1996
DOI: 10.1029/96ja00187
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence patterns for transient magnetic field signatures at high latitudes

Abstract: Impulsive events marked by durations ranging from 5 to 15 min and peak‐to‐peak variations in the H component exceeding 40 nT are common in observations by high‐latitude day side ground magnetometers. We survey observations by a global network of high‐latitude ground magnetometers to distinguish between their proposed causes. Peak event amplitudes and occurrence rates occur prior to local noon in the range of geomagnetic latitudes from 70° to 76°. Although most events can be associated with abrupt changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 72 publications
9
71
1
1
Order By: Relevance
“…However, none of the pressure variations excited a significant response at the location of GOES-8, deep within the dawn mag- Roelof and Sibeck, 1993]. It may also help explain why it is a simple matter to associate TCVs in high-latitude ground magnetograms with SI signatures at low latitudes and geosynchronous orbit [e.g., Sibeck, 1993], but it is rather more difficult to find a corresponding pressure change in the undisturbed solar wind [Sibeck and Korotova, 1996]. Apparently, the effects of the solar wind interaction with the bow shock are far more dynamic than was previously imagined.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the pressure variations excited a significant response at the location of GOES-8, deep within the dawn mag- Roelof and Sibeck, 1993]. It may also help explain why it is a simple matter to associate TCVs in high-latitude ground magnetograms with SI signatures at low latitudes and geosynchronous orbit [e.g., Sibeck, 1993], but it is rather more difficult to find a corresponding pressure change in the undisturbed solar wind [Sibeck and Korotova, 1996]. Apparently, the effects of the solar wind interaction with the bow shock are far more dynamic than was previously imagined.…”
Section: Discussionmentioning
confidence: 99%
“…Several statistical studies have partially addressed the second prediction. Glaßmeier et al (1989), Lanzerotti et al (1991), and Sibeck and Korotova (1996) all reported a strong tendency for transient events in the high-latitude dayside ionosphere to occur prior to local noon, as might be expected for the prevailing spiral IMF orientation. No statistical survey has addressed the third prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Konik et al (1994) and Sibeck and Korotova (1996) reported that transient events observed in the high-latitude dayside ionosphere exhibit only a slight tendency to occur for northward IMF orientations. Rather than providing information about their generation mechanism, this tendency may simply reflect difficulties in identifying the relatively lowamplitude events during the periods of intense geomagnetic activity that are expected for southward IMF orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Konik et al [1994] found that only 15-30% of their studied events could be associated with dynamic pressure variations in the solar wind, while 70% or more were the result of localized reconnection. Sibeck and Korotova [1996] reported that the majority of the impulsive events that they studied were associated with sharp changes in the IMF orientation, but only a few could be associated with changes in the solar wind dynamic pressure. Sitar et al…”
Section: Introductionmentioning
confidence: 99%
“…Ground magnetometers in the high-latitude dayside region regularly observe a variety of pulsations and transient signatures. Sibeck and Korotova, 1996]. However, evidence has been insufficient to conclusively connect any one of these processes with ground signatures.…”
Section: Introductionmentioning
confidence: 99%